Inhalation therapy in cystic fibrosis - Carnovale, Vincenzo; Iacotucci, P.; Cellurale, M.; D'Ippolito, M.; Buonaurio, S.; Celardo, A.; Ferrara, N. (Acta Biomedica Atenei Parmensis, 2014)
In Cystic Fibrosis (CF) inhalation of drugs to treat lung disease has been proven to be highly effective. An increasing number of drugs and devices have been developed for CF lung disease. In this article we will review the current status of inhaled medication in CF, including the various drugs, their modes of administration and indications, and their effects. We will address antibiotics, mucolytics/mucous mobilizers, antiinflammatory drugs, bronchodilators and combinations of solutions. We will review the current knowledge on devices for inhalation therapy with regard to optimal particle sizes and characteristics of wet nebulisers, dry powder and metered dose inhalers.